To What Extent Should Academic Freedom Allow Academics To Criticise Their Universities? - Levine, Pnina; Haydn, Rigby (2022)
The recent case of Gerd Schröder -Turk v Murdoch University has thrown up questions in relation to the extent to which an academic is allowed to criticise the university at which they are employed. What freedom, if any, does an academic have to criticise the practices of their Australian university? Are there any limits to this freedom? Are these limits appropriate? These questions in turn raise questions as to the existence and nature of any right that an academic has to exercise academic freedom in Australia and whether and the extent to which this right may provide an academic with more protection to criticise their university employer than they may have otherwise had and whether this may have unintended, detrimental consequences. Does this right to academic freedom allow academics to criticise their institution whether or not they have a reasonable basis for doing so and if so, should this be the case? This article explores these questions with particular reference to the effect of the Model Code for the Protection of Free Speech and Academic Freedom recommended by former High Court of Australia Chief Justice Robert French and proposes some amendments to this Code.